Respuesta :

Answer:

y-3=3(x-2)

Step-by-step explanation:

y-y1=m(x-x1)

m=3

y-3=3(x-2)

The equation of the line is y-3=3(x-2) if the line that passes through (2, 3) and has a slope of 3 option (B) is correct.

What is a straight line?

A straight line is a combination of endless points joined on both sides of the point.

The correct options are:

y-2 = 3(x - 2)

y-3=3(x-2)

y+ 1 = 3(x-2)

y + 2 / 2 = 2(x-3)

We have:

The line that passes through (2, 3) and has a slope of 3

The slope-point form of the line:

(y - y1) = m(x - x1)

As we know, the ratio that y increase as x increases is the slope of a line. The slope of a line reflects how steep it is, but how much y increases as x increases. Anywhere on the line, the slope stays unchanged (the same).

[tex]\rm m =\dfrac{y_2-y_1}{x_2-x_1}[/tex]

The slope the line m = 3

x1 = 2

y1 = 3

Plug all the values in the slope-point form:

(y - 3) = 3(x - 2)

y - 3 = 3x - 6

y = 3x - 6 + 3

y-3=3(x-2)

Thus, the equation of the line is y-3=3(x-2) if the line that passes through (2, 3) and has a slope of 3 option (B) is correct.

Learn more about the straight line here:

brainly.com/question/3493733

#SPJ6